Pengaruh Adaptabilitas Karir terhadap Intensi Berwirausaha pada Siswa SMKN 9 Bandung Jurusan Tata Boga - Siti Alifa Magfiranisa; Susandari (Bandung Conference Series: Psychology Science, 2024)
Abstract. This study aims to examine the influence of career adaptability on the entrepreneurial intention of students in the 12th grade of the Culinary Arts program at SMKN 9 Bandung. This research uses a quantitative approach with a sample consisting of 102 12th-grade students from the Culinary Arts program at SMKN 9 Bandung, selected using the cluster random sampling technique. Data were collected through a questionnaire using the Career Adapt-Ability Scale-Indonesian Form adapted by Sulistiani et al. (2019) and an entrepreneurial intention scale developed by Maulana and Prihastuty (2020) based on the Theory of Entrepreneurial Event by Shapero and Sokol (1982). Data analysis was conducted using multiple linear regression to determine the influence of each dimension of career adaptability, which consists of career concern, career control, career curiosity, and career confidence, on entrepreneurial intention. The results showed that control, curiosity, and confidence significantly influenced entrepreneurial intention (p<.05), whereas the dimension of career control did not significantly influence entrepreneurial intention (p>.05). Confidence had the largest positive impact on entrepreneurial intention (β=.621), followed by the concern dimension (β=.264). Meanwhile, the curiosity dimension had a negative impact on entrepreneurial intention (β=-.278). The overall contribution of all career adaptability dimensions to entrepreneurial intention was 14.7%. This research can serve as an information source for prospective graduates of the Culinary Arts program at SMKN 9 Bandung to develop their psychological components and become a job creators. Abstrak. Penelitian ini bertujuan untuk mengkaji pengaruh adaptabilitas karier kepada intensi berwirausaha siswa pada kelas 12 jurusan Tata Boga di SMKN 9 Bandung. Penelitian ini memakai pendekatan kuantitatif dengan sampel penelitian terdiri dari 102 siswa kelas 12 jurusan Tata Boga di SMKN 9 Bandung yang dipilih memakai teknik cluster random sampling. Data dikumpulkan melalui kuesioner yang dengan alat ukur Career Adapt-Ability Scale-Indonesian Form yang diadaptasi oleh Sulistiani et al. (2019) dan alat ukur intensi berwirausaha yang dikembangkan oleh Maulana dan Prihastuty (2020) berlandaskan Theory of Entrepreneurial Event dari Shapero dan Sokol (1982). Analisis data dilakukan dengan regresi linier berganda untuk menentukan pengaruh masing-masing dimensi adaptabilitas karier yang terdiri dari career concern, career control, career curiosity dan career confidence terhadap intensi berwirausaha. Hasil analisis menunjukan control, curiosity dan confidence berpengaruh terhadap intensi berwirausaha (p<.05), sedangkan dimensi career control tidak berpengaruh terhadap intensi berwirausaha (p>.05). Confidence memberikan pengaruh positif paling besar terhadap intensi berwirausaha (β=.621), diikuti dengan dimensi concern (β=.264). Sedangkan dimensi curiosity memberikan pengaruh negatif terhadap intensi berwirausaha (β=-.278). Besaran kontribusi seluruh dimensi adaptabilitas karier kepada intensi berwirausaha sejumlah 14.7%. Penelitian ini dapat menjadi sumber informasi calon lulusan SMKN 9 Bandung jurusan tata Boga untuk mengembangkan komponen psikologis mereka dan menjadi pencipta lapangan kerja.